HUBUNGAN ANTARA MASA GESTASI DENGAN KEJADIAN IKTERUS NEONATORUM - Ratuain, Maria Oliva; Wahyuningsih, Heni Puji; Purnamaningrum, Yuliasti Eka (Jurnal Kesehatan Ibu dan Anak, 2015)
The neonatal mortality rate which happens in Indonesia in 2012 is around 32 per 1000. one of the motives which cause mortality in a newborn baby is bilirubin encephalopathy which is a complication of neonatal jaundice. The infants which born at term have a risk as high as60% of neonatal jaundice and it has a risk as high as 80% premature infants. The liver maturation makes the process of bilirubin uptake and conjugation process is slower, especially premature infants. The aim to determine the relationship between gestational age with the incidence of neonatal jaundice. Types of research using observational methods with case-control studies. There are 44 case samples of neonatal jaundice baby and 44 samples of control baby which is non-neonatal jaundice. Research instrument using a data collection format with chi-square analysis of the data. Result: Neonatal Jaundice in premature babies 59.1% and 40.9% in full-term infants. Results of the chi-square fest p-value 0.033 <0.05 with OR 2,5 (CI 1.070 to 5.970). Conclusion: There is a correlation between gestational age with the incidence of neonatal jaundice. Preterm gestation 2.5 times greater risk of increasing the incidence of neonatal jaundice.